The Need for and Cost of Selected Trade Facilitation Measure Relevant to the WTO Trade Facilitation Negotiations: A Case Study of Nepal - Pushpa Raj Rajkarnikar (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
Trade facilitation has been a longstanding and traditional feature of GATT, which is expected to have serious implication for developing member countries. This study aims to evaluate the need for and the cost of implementing trade facilitation measures in Nepal in the context of the ongoing WTO negotiation. Nepal initiated market oriented economic reforms in 1985. Trade liberalization under the economic reform was significant. However, trade facilitation has got due attention only in recent years. HMG introduced ASYCUDA in selected custom offices and implemented a three years (2003-2006) Customs Reform Action Plan in the process of TF.
Keywords: F1; 330; GATT; WTO; Trade Facilitation; Nepal